Morphing of geometric composites via residual swelling. Issue 29 (7th August 2015) - Pezzulla, Matteo; Shillig, Steven A.; Nardinocchi, Paola; Holmes, Douglas P.
<x xml:space="preserve">Abstract</x> Understanding and controlling the shape of thin, soft objects has been the focus of significant research efforts among physicists, biologists, and engineers in the last decade.